Novel heterozygous ASH1L nonsense variant involved in mild intellectual disability - Liao, Baoqiong; Xie, Wuming; He, Shuwen (Frontiers in neurology, 2025)
Mutations in ASH1L have been associated with a range of phenotypes, including intellectual disability (ID), autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), seizures, as well as differences in skeletal, muscular, and sleep functions. In this study, we describe a patient diagnosed with mild ID, and whole-exome sequencing (WES) of the family identified a novel heterozygous nonsense variant, NM_018489.2: c.2479A > T (p.Lys827*), located in exon 3 of ASH1L , which was predicted to be pathogenic. The nonsense variant in the mild ID patient may disrupt ASH1L function by destabilizing its spatial conformation, leading to decreased activity of the catalytic H3K36 methylation, thereby affecting neurological function. A review of reported ASH1L nonsense mutations to explore genotype–phenotype correlations suggested that these variants typically result in a loss of function. Our findings contribute to understanding the neurodevelopmental pathogenesis of mild ID in patients with the ASH1L nonsense variant mutation.